THE EFFECT OF BUILDING GEOMETRIC SHAPE AND ORIENTATION ON ITS ENERGY PERFORMANCE IN VARIOUS CLIMATE REGIONS - Remon Lapisa (GEOMATE Journal, 2019)
Building thermal characteristic is one of the key factors in energy consumption. Many studies have been conducted to improve the building thermal performance for energy efficiency. In fact, building energy consumption and thermal comfort are affected by several factors, such as building geometry, structural design, building envelope materials, environment, local climate and occupancy patterns of the occupants within the occupied zone. In the building geometry aspect, two important parameters that have significant impacts on building thermal performance are building shape and orientation. The aim of this study is to evaluate the impact of these parameters on building energy consumption. In the first part, the description of building characteristics is completely explained. Extensive numerical simulations using a coupling of TRNSYS (R) and CONTAM (C) have been performed under mono-zone building thermal design. Numerical simulation results showed that a compact building shape and appropriate building orientation can reduce the energy consumption for heating and cooling systems up to 81% depending on the geographical conditions where the building is located.